REAKSI PASAR DAN INFORMASI ASIMETRI TERHADAP TINDAKAN PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ari Dewi Cahyati (JRAK: Journal of Accounting Research and Computerized Accounting, 2010)
The investor’s attention on the net income number without regard to the procedures used, has encouraged management to carrry out earnings management, include within earnings management is income smooting. Income smoothing is the way to reduce earnings variability over a number of period as movement toward unexpected level of reported earning. Objective of this study is to anaylize 1) market reaction and asymetri information surounding the company announcement date 2)Effect assymetry informatin on stock price. The sample that used is the company with eckel index less than one (i.e to indicate income smoothing practice). Using purposive sampling method this study examine 39 companies listed in the Indonesian stock exchange. Market reaction is measured as cumulative abnormal return five days surrounding the companie earnng announceent date. T-test was used to examine market reaction and asymetri information surrounding the companies earnings management date. Regresion linear was used to examine effect of asymetri informationtoward share price.Result of this study indicate that 1) there is income smoothing practise in Indonesian stock exchange 2) There is significant market reaction asymetri information surrounding the companies earnings management 3)There is significant positive effect of asymetri information toward share price.